A Two-Component Regulatory System in Transcriptional Control of Photosystem Stoichiometry: Redox-Dependent and Sodium Ion-Dependent Phosphoryl Transfer from Cyanobacterial Histidine Kinase Hik2 to Response Regulators Rre1 and RppA - Ibrahim, Iskander M.; Puthiyaveetil, Sujith; Allen, John F. (Frontiers in Plant Science, 2016)
I hereby submit the above-titled manuscript for publication in Frontiers in Plant Science. The research reported is original and novel. No part of it is submitted for publication elsewhere. We report on regulation and interactions of a unique histidine sensor kinase, Hik2. Hik2 is found in all known cyanobacteria, but has no previously identified functional response regulator. Here we show that it transfers phosphate rapidly, in vitro, to two response regulators, termed Rre1 and RppA. Hik2 is of special importance in being indispensable to cyanobacteria, and in being the closest cyanobacterial homologue of the uniquely conserved Chloroplast Sensor Kinase (CSK), which couples photosynthetic electron transport to gene transcription. Hik2 function is so important that it has survived the transition from cyanobacterium to eukaryotic sub-cellular organelle. Hik2 is likely to be a redox sensor involved in adjustment of the stoichiometry of photosystems I and II of oxygenic photosynthesis. We show that Hik2 also responds to the specific presence of sodium ions. These regulatory controls and the bifurcated signal transduction pathway indicated by two response regulators lead to a proposal for integration of photosynthetic light-acclimation with response to salt stress.